Fragmented Stories, Unified Brands: How Consumers Reconstruct Meaning Across Multiple Digital Platforms - Sadeh, Hamdi (Journal of Digital Marketing and Communication, 2026)
Despite growing scholarly attention to fragmented brand narratives, existing research adopts brand-centric perspectives, leaving a critical gap in understanding how consumers reconstruct meaning from dispersed digital fragments. This study addresses this gap by investigating the interpretive strategies consumers employ to derive coherent brand understanding across multiple platforms. Theoretically grounded in transmedia storytelling, sense-making theory, and platform affordances, this research adopts a qualitative, interpretivist approach utilizing reflexive thematic analysis. Data were collected through semi-structured interviews with 25 digitally active consumers from Palestine, Jordan, UAE, Saudi Arabia, and Egypt, selected through purposive sampling to ensure diversity in age (21–48), professional background, and digital literacy. Findings reveal four key insights: First, consumers normalize fragmentation as an expected feature of digital branding rather than a barrier. Second, they actively engage in cross-platform sense-making through systematic cross-checking and critical evaluation of brand messages. Third, trust operates as a dynamic construct negotiated through algorithmic transparency and influencer authenticity, not as a passive brand attribute. Fourth and most significantly, emotional coherence—consistency of affective tone and values across platforms—emerges as more influential in shaping perceived brand unity than strict message consistency. This study contributes to digital branding literature by shifting focus from brand-controlled messaging to consumer-centered meaning reconstruction, offering a conceptual model that positions brand coherence as an emotional and symbolic consumer outcome rather than a managerial output. Practical implications include platform-specific storytelling that prioritizes emotional alignment over message uniformity, alongside policy recommendations for transparent algorithmic practices and influencer governance in emerging digital markets.